Swine Host Protein Coiled-Coil Domain-Containing 115 (CCDC115) Interacts with Classical Swine Fever Virus Structural Glycoprotein E2 during Virus Replication - Elizabeth A. Vuono; Elizabeth Ramirez-Medina; Keith Berggren; Ayushi Rai; Sarah Pruitt; Ediane Silva; Lauro Velazquez-Salinas; Douglas P. Gladue; Manuel V. Borca (Viruses, 2020)
Interactions between the major structural glycoprotein E2 of classical swine fever virus (CSFV) with host proteins have been identified as important factors affecting virus replication and virulence. Previously, using the yeast two-hybrid system, we identified swine host proteins specifically interacting with CSFV E2. In this report, we use a proximity ligation assay to demonstrate that swine host protein CCDC115 interacts with E2 in CSFV-infected swine cells. Using a randomly mutated E2 library in the context of a yeast two-hybrid methodology, specific amino acid mutations in the CSFV E2 protein responsible for disrupting the interaction with CCDC115 were identified. A recombinant CSFV mutant (E2ΔCCDC115v) harboring amino acid changes disrupting the E2 protein interaction with CCDC115 was produced and used as a tool to assess the role of the E2–CCDC115 interaction in viral replication and virulence in swine. CSFV E2ΔCCDC115v showed a slightly decreased ability to replicate in the SK6 swine cell line and a greater replication defect in primary swine macrophage cultures. A decreased E2–CCDC115 interaction detected by PLA is observed in cells infected with E2ΔCCDC115v. Importantly, animals intranasally infected with 105 TCID50 of E2ΔCCDC115v experienced a significantly longer survival period when compared with those infected with the parental Brescia strain. This result would indicate that the ability of CSFV E2 to bind host CCDC115 protein during infection plays an important role in virus replication in swine macrophages and in virus virulence during the infection in domestic swine.